Groundwater discharge dynamics into a salt marsh tidal river. (5th March 2019) - Peterson, Richard N.; Meile, Christof; Peterson, Leigha E.; Carter, Matthew; Miklesh, David
Abstract: Exchange of groundwater is an important transfer mechanism for nutrients and pollutants between coastal aquifers and surface waters. Constraining such exchange in salt marshes - where biological productivity and biogeochemical cycling rates are among the highest of all coastal ecosystems – is vital for understanding ecosystem function and vulnerability. Here, we quantify groundwater discharge into the tidal Duplin River from the adjoining salt marsh near Sapelo Island, Georgia using high spatial and temporal resolution field measurements of radon-222. Field campaigns occurred for several weeks each summer during 2013, 2015, and 2016. Spatial surveys reveal a general increase in radon activity upstream through the Duplin River, which may result from either higher groundwater discharge or lower mixing rates in the headwaters. To distinguish between these possibilities, we use a radon mass balance model to determine groundwater input. We find that groundwater discharge (normalized to inundated marsh surface area) to the headwaters average 5.1–5.8 cm 3 /cm 2 marsh/day across all three field campaigns, which are comparable to those to the main channel (averaging 6.0–6.5 cm 3 /cm 2 marsh/day across all three field campaigns). Our work reveals a positive relationship between aerial extent of marsh inundation and groundwater discharge into the Duplin River. Discharge is generally maximal during falling tide, reflecting a hydraulic gradient driver, but also is significant prior to high tide, indicative of sediment compression as a driver of groundwater inputs. Constraining the relationship between marsh inundation and resulting groundwater dynamics is an integral aspect to assessing how salt marsh circulation processes may respond to intensifying inundation (from reduced sediment supply, subsidence, and/or rising sea levels). Graphical abstract: Image 1 Highlights: Radon was used to trace groundwater inputs to the Duplin River near Sapelo Island. Radon concentrations generally increase upstream and reach maxima during low tide. Groundwater inputs peak during ebb tide and are highest in the headwaters. A larger inundated marsh area yields greater groundwater discharge volumes.